2020
DOI: 10.4269/ajtmh.20-0301
|View full text |Cite
|
Sign up to set email alerts
|

False Positivity of rK39 Test in Five Chronic Myeloid Leukemia Cases from Bihar, India: A Possible Challenge to Leishmaniasis Diagnosis

Abstract: A rapid and noninvasive rK39 rapid diagnostic test (RDT) is the best and most reliable tool for visceral leishmaniasis (VL) screening in the field. However, splenic and bone marrow aspiration remain two gold standard methods for microscopic identification of Leishmania donovani (LD) bodies and confirmatory diagnosis of VL. Five patients with signs and symptoms of fever, loss of appetite, loss of weight, hepatomegaly, and massive splenomegaly were found to be false positive with the rK39 RDT. These patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…The rK39 rapid diagnostic tests (RDT) is the only RDT that has been successfully developed in VL; it was found 90% sensitive and 100% specific in India, during a time of high prevalence of VL, and the test is used in the KAEP in the ISC ( Kumar et al., 2001 ). However, false positive results may occur in malaria, tuberculosis, liver cirrhosis and chronic myeloid leukaemia ( Topno et al., 2020 ). In a Cochrane review, the rK39 immunochromatographic test (RDT) showed overall sensitivity in the ISC was 91.9% (95% CI 84.8-96.5) vs 85.3% (95% CI 90.0-99.5%) in East Africa.…”
Section: Resultsmentioning
confidence: 99%
“…The rK39 rapid diagnostic tests (RDT) is the only RDT that has been successfully developed in VL; it was found 90% sensitive and 100% specific in India, during a time of high prevalence of VL, and the test is used in the KAEP in the ISC ( Kumar et al., 2001 ). However, false positive results may occur in malaria, tuberculosis, liver cirrhosis and chronic myeloid leukaemia ( Topno et al., 2020 ). In a Cochrane review, the rK39 immunochromatographic test (RDT) showed overall sensitivity in the ISC was 91.9% (95% CI 84.8-96.5) vs 85.3% (95% CI 90.0-99.5%) in East Africa.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, a small number of FC and RC tested positive by rK39 RDT. We can not exclude that some of these positive tests might be false positive ( 63 ). No seroconversion of those who tested negative at T1 was observed at T2.…”
Section: Discussionmentioning
confidence: 99%
“…Along with spurious chemistry results, false‐positive serological results occur in humans secondary to paraproteinemia, both because of hematological malignancies (such as multiple myeloma) and secondary to benign age‐related increases in immunoglobulin levels. This includes false‐positive Galactomann antigen tests for aspergillosis, 8,28,29 false‐positive serological tests for syphillis, 5,29,30 and false‐positive rK39 rapid diagnostic tests for leishmaniasis 6 . There are also false‐positive results for a wide range of infectious agents (viral, bacterial, and protozoal) in human patients receiving immunoglobulin therapy IV 31‐35 .…”
Section: Discussionmentioning
confidence: 99%
“…This includes false-positive Galactomann antigen tests for aspergillosis, 8,28,29 falsepositive serological tests for syphillis, 5,29,30 and false-positive rK39 rapid diagnostic tests for leishmaniasis. 6 There are also false-positive results…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation